Formation of state audit classification model - Бардаш, Сергій Володимирович; Баранюк, Юрій Романович (Technology audit and production reserves, 2016)
The object of research is classification of state audit. Today in the domestic theory and practice of control there is no clearly formed conceptual apparatus on state audit, which is defined as a «manifestation» of the state financial control – type, shape, type, method and so on. Methods of abstraction, analysis and systematization to determine significant differences and improving state audit conceptual apparatus, method of synthesis for the formulation of research findings are used in the research. Results of comparative analysis of existing classifications of state audit are revealed, validity of its identification as the form and type of the control is examined. Feasibility of state audit recognition as a form of the control is proved on the basis of awareness of its polymorphism. Its classification is made. It shows the current state of its development, so it can be the subject of critical evaluation and substantial improvement. The approach to the classification of public audit is based on the knowledge that public resources are its integrated object, and state audit should be viewed as a form of control, the widespread introduction of which in Ukraine provide certain guarantees for civil society in effective management of central executive bodies and local government bodies of public resources. The results of the study: the concept of «form of control», «type of control», «subtype of control» are specified and relationship between them is defined; it is found that state audit in the system of knowledge about state control as a kind of practice should be considered as its form, which further classification will lead to allocation of its types and subtypes; classification of public audit is developed. These results provide new conditions for development of the theory of state audit and its practical implementation, including extending to the entire list of public resources, as well as increase of state audit bodies.